Measurement of thermal sweating at rest and steady-state exercise in healthy adults: Inter-day reliability and relationships with components of partitional calorimetry - Jenny Peel (PLOS ONE, 2022)
Objective. Inter-day reliability of sweat measurements, including the absorbent patch and modified iodine-paper techniques, at rest and exercise were evaluated. We further evaluated the effect of iodine paper size and the method of establishing sweat gland activation (sweat gland counting or surface area covered) on reliability. Furthermore, the relationships between all measurement techniques and metabolic heat production [Ḣprod] and evaporative requirement for heat balance [Ėreq] were determined.Method. Twelve participants were assessed for whole-body sweat loss (WBSL), local sweat rate (LSR; absorbent patch) and sweat gland activation (SGA; iodine-paper) during rest and sub-maximal cycling at ~200, ~250 and ~300 W/m2 Ḣprod in the heat. Variations in iodine paper (1 x 1 cm-9 x 9 cm) were used to quantify SGA by counting sweat glands or surface area covered. The ‘optimal’ area of SGA was also determined based on the highest density of recruited glands. Results. All measures of the sweating response were positively related with Ḣprod and Ėreq (r = 0.53-0.84), with the 9 x 9 cm and 6 x 6 cm iodine paper sizes being the strongest (r = 0.66-0.84) for SGA. Superior inter-day reliability was found for all measures during exercise (CV% = 6-33.2) compared to rest (CV% = 33.5-77.9). The iodine-paper technique was most reliable at 9 x 9 cm (CV% = 15.9) or when the 1 x 1 cm (CV% = 17.6) and 3 x 3 cm (CV% = 15.5) optimal SGA was determined, particularly when measuring the sweat gland number.Significance. WBSL, LSR and SGA measurement techniques are sufficiently reliable to detect changes in thermal sweating typically reported. We recommend 9 x 9 cm paper sizes or 1 x 1 cm-3 x 3 cm optimal areas, using either gland counting or surface area to determine SGA.